TALENT IDENTIFICATION PRACTICES AND CHALLENGES OF COACHES: IN IDENTIFYING TALENTED YOUNG FOOTBALL PLAYERS - Alemmebrat Kiflu (Dr.), (Sport Scientific And Practical Aspects, 2025)
ʹYou reap what you sowʹʹ. The foundation of future success of elite football players that represent the country football lies at grass root level through proper talent identification and development process. This should be strongly synchronized. The aim of this paper was to examine the current talent identification practices of Ethiopian youth sports academy football coaches and their main challenges while implementing the identification process. To investigate the problem, mixed research design was employed. In-depth interview as well as a five point Likert item questions were used as a means to obtain valid and reliable data among 76 study participants aged ranged between 25 to 65 (± 5) using purposive and snowball sampling method. The interview was analysed qualitatively while SPSS version 17 software was applied as a statistical tool for the analysis of quantitative data. Results obtained from the triangulated data indicated that coaches identify talented young football players based on their overall performance at an arranged trail game /competition/ situation. Great attention was given to technical and tactical skills. Few efforts have been carried out to implement on the potential predictors of talent, like anthropometric, physiological, psychological and sociological predictors but it had not purely a scientific basis. This study also revealed that coaches’ problems were various, but broadly categorized in four pillars as technical, economical, administrative and sociocultural. It is there for concluded that based on its responsibility and mission, the sport academy should give due attention to the magnitude of problems in discussing the problem of the coaches with higher institution professionals and other stakeholders, besides to this, talent identification process and tasks should never be left to the coaches alone, rather talent scouts should be invited and participated actively for a better result.